Replication priority of hepatitis C virus genotype 2a in a Chinese cohort - Zhen Yang; Yongxin Yu; Hongzhong Zhang; Guifang Shang; Jialiang Gao; Jian-Dong Jiang; Zonggen Peng (Elsevier, 2014)
HCV genotypes have been documented in clinical practice. The aim of this study was to determine the replication priority of different HCV genotypes in a Chinese HCV positive cohort. Serum samples from 491 apparently healthy Chinese blood donors testing positive for HCV antibodies and naive to antiviral drug therapy were tested. Genotyping analysis showed that genotypes 1b and 2a were predominant and accounted for 77.6% of the HCV infections. Among the genotype groups, individuals infected with genotype 2a had an HCV RNA viral load (108 copies/mL) about 200-fold (lg, 2.3) greater than those infected with other genotypes (104-105 copies/mL) indicating a replication priority of genotype 2a. However, there was no correlation between HCV genotype and antibody response suggesting that the amplification advantage of genotype 2a results from a favorable interaction with the host cellular environment. In conclusion, HCV genotypes 1b and 2a are the predominant genotypes in China and genotype 2a possesses a significant replication priority compared with the other genotypes. This suggests the existence of host cellular factors that may act as drug-targets for entirely clearing HCV infection in the future.